Hazard Management in Tourism: A Case Study of The Senaru-Sembalun Hiking Trail, Mount Rinjani National Park, Indonesia - E. K. S. Harini Muntasib; Fitri Nadhira; Resti Meilani (Institut Pertanian Bogor (IPB University), 2019)
Mount Rinjani (3726 masl) is the second-highest volcano in Indonesia with a newer active volcano called Mount Barujari (2376 masl) inside its crater. The mountain has become the center of tourist destinations in West Nusa Tenggara Province, with hiking as the most popular activity carried out by visitors. This study aimed to identify physical and biological hazard potentials and activities that may put visitors at risk to prepare hazard management recommendations. We carried out an interview and field observation for the study in April 2018. We used the United Nations Environment Programme (UNEP) risk assessment as a reference in biological and physical hazard analysis, and the National Patient Safety Agency for human activities. We also used ArcGIS 10.1 software to develop a map of hazard potentials. Cliff (physical hazard), tree roots (biological hazard), and running (activity) were hazards with the highest risks. All four management options offered by the UNEP, i.e., reducing risk, accepting the tolerable risk, avoiding risk, and transferring risk, were applicable in this area. We proposed that the management considering to increase local community and visitors' knowledge of hazards as a preventive measure while continuing to provide repressive measures.